Toward energy security in ASEAN: Impacts of regional integration, renewables, and energy efficiency - Yang Liu; Sheng Zhong; Dina Azhgaliyeva (Asian Development Bank Institute (ADBI), 2019)
ASEAN countries share the common challenge of energy security, which consists of meeting rising demand for energy in a secure, affordable and sustainable manner. This paper extends the gravity model to estimate the effects of economic integration, renewable energy supply and energy efficiency on energy security. By extending the gravity model, our model specifications introduce a series of key variables to capture the deployment of renewable energy, energy efficiency and level of regional economic integration. Three measures are crucial to this task: ensuring renewable energy supply, energy efficiency improvements, and stronger economic integration. Using annual data across 440 countries over the period 1995-2016, we demonstrate the role of renewable energy supply, energy efficiency improvements and economic integration in bilateral energy trade. Based on our findings, policy recommendations are provided to help ASEAN decision makers prescribe future energy security policy.
Keywords: F14; F15; Q43; Q42; 330; energy security; regional trade agreement; ASEAN; energy trade; renewable energy; energy efficiency